Union Organizing in the Canadian Banking Industry, 1940-1980 - Smith, Julia Maureen (Trent University, 2016)
In this dissertation, I examine union organizing in the Canadian banking industry between 1940 and 1980. By demonstrating that bank workers consistently sought to unionize throughout the twentieth century, I challenge claims that bank employees and other private sector white-collar workers have low rates of unionization because they are not interested in unions or suffer from false consciousness. This research also suggests, however, that many bank workers saw themselves as different from blue-collar industrial workers; the lived reality of bank work as precarious, poorly paid, and rife with gender inequality intersected with ideas about professionalism and aspirations of advancing up the career ladder. Banks, unions, and workers drew on these ideas and experiences in their arguments for and against unionization. I also look at why previous organizing efforts did not establish a strong union presence in the banking industry. Most of these attempts failed, I argue, due to several key issues, including the banks’ anti-union activity, federal and provincial labour board decisions, and labour movement disputes over ideology, jurisdiction, and strategy. The banks consistently opposed unionization and used a variety of tactics to thwart union organizing, both overtly and covertly. The state, in the form of labour legislation and labour boards, provided unions and workers with some means by which to compel the banks to recognize unions, negotiate contracts, and deal with employee grievances; however, state action and inaction more often worked to undermine union organizing. The attitudes and strategies of high-ranking labour movement officials also shaped the outcome of union drives in the banks. Between 1940 and 1980, the mostly male labour leadership repeatedly used top-down organizing strategies and appointed male organizers with no experience of bank work to oversee union drives in a sector with an increasingly feminized workforce; labour leaders’ inability or unwillingness to reflect on this approach and to support grassroots campaigns and alternative strategies hindered bank union organizing. I thus highlight the intersection of gender and class and reveal how these factors have historically shaped the labour movement bureaucracy, union organizing, and the relationship between labour and the state. Author Keywords: banks, gender, labour bureaucracy, trade unions, union organizing, white-collar workers.